Optimasi Parameter Model Mock Pada Aliran Sungai Lematang-Lebak Budi - Alharia Dinata (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2018)
Development and control of water resources sometimes there are problems regarding hydrological data on watersheds that are incomplete or even nonexistent. The purpose of this study is to optimize the parameters of the Mock model on the Lematang - Lebak Budi river. The mock model is a common method that is often used in Indonesia because this model is quite simple, easy to use, relatively little data used, and gives results that are close to the data in the field. The results of the analysis show that the parameter optimization of the Mock model on th Lematang - Lebak Budi river has a Correlation Coefficient (R) of 0.98 and Volume Error (VE) of 2.52% and the results of the validation values are R = 0.75 and VE = 2.03 %. Based on the results of the optimization and validation of the parameters of the Mock model in the Lematang – Lebak Budi river, this high level of reliability can be seen from the value of R approaching the number 1 and VE ranging from 0 - 5%.